2011
DOI: 10.1158/0008-5472.can-10-2788
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Synergizes with Type I Interferons through Systemic Dendritic Cell Reactivation and Induction of Immunogenic Tumor Apoptosis

Abstract: Successful chemotherapy accounts for both tumor-related factors and host immune response. Compelling evidence suggests that some chemotherapeutic agents can induce an immunogenic type of cell death stimulating tumor-specific immunity. Here, we show that cyclophosphamide (CTX) exerts two types of actions relevant for the induction of antitumor immunity in vivo: (i) effect on dendritic cell (DC) homeostasis, mediated by endogenous type I interferons (IFN-I), leading to the preferential expansion of CD8a þ DC, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
248
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 315 publications
(254 citation statements)
references
References 48 publications
(64 reference statements)
5
248
0
1
Order By: Relevance
“…CTX exerted its effects preferentially on the CD8a-expressing-DC subset, determining an initial ablation of lymphoid organ-resident CD8a þ DCs, followed by overshoot replenishment after drug discontinuation. 20,21 Data from our laboratory have revealed that, after CTX administration, CD8a þ DCs migrate to the tumor site where they cross-present tumor-associated antigen ( Figure 2). The platinum-based compound cisplatin was also reported to modulate the percentages of myeloid cells by increasing DCs and eliminating myeloid-derived suppressor cells (MDSCs), thus favoring immune effector responses in melanoma-bearing mice.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…CTX exerted its effects preferentially on the CD8a-expressing-DC subset, determining an initial ablation of lymphoid organ-resident CD8a þ DCs, followed by overshoot replenishment after drug discontinuation. 20,21 Data from our laboratory have revealed that, after CTX administration, CD8a þ DCs migrate to the tumor site where they cross-present tumor-associated antigen ( Figure 2). The platinum-based compound cisplatin was also reported to modulate the percentages of myeloid cells by increasing DCs and eliminating myeloid-derived suppressor cells (MDSCs), thus favoring immune effector responses in melanoma-bearing mice.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…94 The degree of TCD correlates with clinical outcome in several tumor settings. 95,96 Some chemotherapeutics, including anthracyclines, oxaliplatin and CTX, are unique in their capacity to induce an immunogenic type of TCD, 21,97 thereby converting dying tumor cells into adjuvanted-endogenous vaccines. The rational base of vaccination is that tumor antigens must be captured by activated DCs, which would activate CD4 and CD8 T-cell-mediated adaptive immune responses.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
See 3 more Smart Citations